2022
DOI: 10.1080/17482631.2022.2088456
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent bonds, positive and negative emotions, and expectations in teachers’ perceptions of relationship with their students with ADHD

Abstract: A growing body of research has been focusing recently on the life and well-being of students with attention-deficit/hyperactivity disorder (ADHD) and also on the well-being of their teachers. However, there is a need for in-depth, qualitative insights into ADHD issues from the teachers’ perspectives. Therefore, the main aim of this qualitative study was to use thematic analysis to explore how teachers perceive the relationship with students with ADHD and the factors that influence the quality of this relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 88 publications
0
1
0
Order By: Relevance
“…These findings mirror previous research which reported that post‐primary teachers viewed the behaviour of students with ADHD as disruptive (Krtek et al., 2022) and similar attitudes have also been reported among primary school teachers in Ireland (Ward, 2014) and internationally (Amha & Azale, 2022; Mahdi & Al‐Juboori, 2021; Schatz et al., 2021). Perceptions that students with ADHD negatively impact teaching and learning, reduce the amount of time available for others, and thereby compromising everyone's ability to learn are also supported by earlier research among Canadian elementary teachers (Blotnicky‐Gallant et al., 2015).…”
Section: Findings and Discussionsupporting
confidence: 89%
“…These findings mirror previous research which reported that post‐primary teachers viewed the behaviour of students with ADHD as disruptive (Krtek et al., 2022) and similar attitudes have also been reported among primary school teachers in Ireland (Ward, 2014) and internationally (Amha & Azale, 2022; Mahdi & Al‐Juboori, 2021; Schatz et al., 2021). Perceptions that students with ADHD negatively impact teaching and learning, reduce the amount of time available for others, and thereby compromising everyone's ability to learn are also supported by earlier research among Canadian elementary teachers (Blotnicky‐Gallant et al., 2015).…”
Section: Findings and Discussionsupporting
confidence: 89%
“…When teachers are involved in the process of regulating students' emotions, such as students reaching out to the teacher for help or to calm and comfort themselves, their knowledge level is clearly seen to reach a higher level. The importance of teachers towards the emotional regulation of SEN students has been stated in previous studies (Poulou & Denham, 2022;Spilt et al, 2021;Mainhard et al, 2018) and is interconnected with the relationship between teachers and students (Krtek et al, 2022;Ewe, 2019). In other words, when a positive relationship between teacher and student is achieved, the level of teacher's knowledge of SEN students' emotional regulation can increase due to increased involvement in the emotion regulation process.…”
Section: Special Education [Se] E-issn: 2821-3017mentioning
confidence: 78%
“…However, experiences in harsh positions before diagnosis indicated a need for approaches that went beyond medication and that involved the environments, such as teachers and families. In this regard, Krtek et al ( 2022 ), emphasized that the teacher’s knowledge of ADHD determinants, regulation of ambivalent emotions and empathy increased the quality of the teacher-ADHD- student-relationship.…”
Section: Discussionmentioning
confidence: 99%